Inovasi Produk Minyak Kelapa dan Penguatan Literasi Keuangan: Pemberdayaan Ibu-Ibu PKK Menuju Kemandirian Ekonomi Rumah Tangga - Wulandari, Ika; Sri Utami, Endang; Susanto, Djaelani (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to empower members of the PKK women’s group through the transfer of technology in processing virgin coconut oil (VCO) into herbal balm products, accompanied by business financial management mentoring to promote economic self-reliance in Padukuhan Kenteng, Gunungkidul. The program was implemented using a Participatory Rural Appraisal (PRA) approach, with activities comprising counseling sessions, training, and mentoring. Program evaluation employed structured pre-test and post-test questionnaires, supported by observations of practical activities and interviews. Data were analyzed using descriptive and comparative methods, as well as qualitative analysis. Based on the program outcomes, all training components demonstrated significant improvement following the intervention. Participants’ understanding and skills in coconut utilization, VCO production, and herbal balm processing increased from approximately 25–45% prior to the program to around 85–90% after its implementation. Meanwhile, competencies in financial management, including the calculation of cost of production and pricing strategies, also improved from approximately 50–55% to 90–95%, indicating the effectiveness of the program in enhancing both technical and managerial capacities. Overall, this activity is expected to foster community empowerment that ultimately leads to increased household income and family economic independence.